EFEKTIFITAS KOMUNIKASI SEBAGAI KATALISATOR BERKEMBANGNYA POST TRUTH CERDASKAN MILENIAL BERMEDIA SOSIAL DI KOTA MAKASSAR - Mitha Mayestika Kuen; Fyan Andinasari Kuen (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
The post truth era can be called the era of specific social shifts involving opinion makers and mainstream media. Competition of facts and hoaxes and lies to gain public trust. The mainstream media that was once considered one of the sources of truth is the current mainstream media must accept the fact that currently the barrier between lies and truth, non-fiction fiction fraud and honesty is very thin. In simple terms Post-truth can be interpreted that rather than looking for the community's truth, it is more justifying the information obtained. The improper use of social media is an implication of the presence of information technology which is a catalyst for the development of Post-truth, digital technology can produce its own reality, such as what has been scheduled in the agenda setting interest groups, so the separation between markers (signified) and markers ( signifier) is the impact of this situation. The purpose of this study, is to obtain data related to how the effectiveness of Post-truth communication among Makassar City youth in social media has a more intellectual impact or has a negative impact. Quantitative descriptive research methods with a qualitative approach. socializing the habit of Self Censoring, which is not directly trusting information or news even if it is viral before proving it to find out that news is hoax, fake news, fake news, news according to facts or truth (post truth), so the results of this study are the effectiveness of communication as a catalyst The development of post truth brings positive things for millennial adolescents, especially in Makassar City.